PERLINDUNGAN HUKUM BAGI PARA PIHAK DALAM E-COMMERCE SEBAGAI AKIBAT DARI GLOBALISASI EKONOMI. - Lathifah Hanim (Jurnal Pembaharuan Hukum, 2014)
Globalization's impact on the development of technological advances free trade between countries. through international trade spawned free trade rules and more focus on the development of a free market, quickly in a life without limits. The realization of the consequences of free trade globalization is the emergence of the phenomenon of Electronic Commerce. The research method used is normative juridical. legal research literature is legal research conducted by examining the library materials or secondary data. The results obtained that legal protection for parties in e-commerce as a result of economic globalization include the two sides are in agreement and outside the Agreement, as well as E-Commerce Transactions settings in Act No. 11 of 2008 can be described as the need for the existence of an Institution Certification Reliability to certify to the party who will conduct electronic transactions (Article 10); Setting the implementation of the Electronic Transactions (Article 17 Paragraph (3)); Regulation on Electronic Contract for Electronic Transactions (Article 18 Paragraph (1)); Dispute Resolution on Electronic Transactions (Article 18, Paragraph (3)); Electronic system as a system implementation Electronic Transactions (Article 19); Regulation on Electronic Agents as intermediaries in Electronic Transactions (Article 21 and 22).